Impacts of Surface Water Quality in the Awash River Basin, Ethiopia: A Systematic Review - Assegide, Endaweke; Alamirew, Tena; Bayabil, Haimanote; Dile, Yihun T.; Tessema, Bezaye; Zeleke, Gete (Frontiers in Water, 2022)
Water quality impairment, due to anthropogenic activities and limited enforcement capacity, is a rapidly growing threat to water security as well as public health in developing countries. Cumulative effects of deteriorating water quality undoubtedly put pressure on public health and socio-economic developments. For example, most industries in Ethiopia discharge their effluent directly into freshwater systems without any treatment process. The problem is severe for rivers such as the Awash that pass through major cities. Although there were a few studies that looked into the issue, there is a lack of comprehensive water quality impact assessment on agriculture, health, and socio-economics. This article systematically summarizes current research on water quality issues in the Awash River Basin to generate comprehensive information that captures the water quality status of the river and impacts of water contamination, and identify information and management gaps. Results showed that water quality degradation along the river course and in selected tributaries exceeds water quality standards by the WHO and national guidelines. For example, E-coli bacteria concentration in two tributaries, Tinishu and Tiliku Akaki, reach up to 6.68 and 6.61 billion CFU 100 ml/L. Virological profile of creeks receiving wastewater from hospitals in the City of Addis Ababa contains coliphages levels reaching as high as 5.2 × 103 pfu/100 ml for urban rivers and up to 4.92 × 103 pfu/100 ml. Heavy metals that far exceed the tolerable levels for humans were also detected in vegetables produced using impaired water. Heavy metals such as Cd, Cr, Cu, Hg, Ni, and Zn were detected in potato, Zn and Hg in Cabbage, and Cr in onion and red beet. Lettuce irrigated with Akaki river water found to contain 0.263 (Cd), 420 (Fe), 13.44 (Zn), 7.87 (Cr), 7.49 (Cu), and 6.55 (Pb) in mg/kg both in excess of WHO guideline. In addition, a high concentration of Cr has been also found in fish tissues. There has never been a systematic evaluation of the impact of contaminated water in the Awash Basin. Comprehensive impact of water quality investigation that takes into account the different pollutants dynamic needs to be made to protect the well being of downstream beneficiaries including the aquatic ecosystem. In conclusion the systematic review has shown that for a river that cross-through emerging mega-city like Addis Ababa, the human and ecosystem health impact of aquatic ecosystems pollution should not afterthought action